Translating genomics research into control of tuberculosis: lessons learned and future prospects - Warner, Digby F (Genome Biol, 2014)
Genomics research has enabled crucial insights into the adaptive evolution of Mycobacterium tuberculosis as an obligate human pathogen. Here, we highlight major recent advances and evaluate the potential for genomics approaches to inform tuberculosis control efforts in high-burden settings.